Zróżnicowane ramy prawne ojcowskiej władzy rodzicielskiej obowiązujące na ziemiach polskich w pierwszej połowie XIX wieku - Żółciński, Zbigniew J. (Poznańskie Towarzystwo Przyjaciół Nauk we współpracy z Zakładem Historii Wychowania, WSE UAM, 2013)
The law itself has a proven impact on people’s everyday lives. It is usually the product of compromise, which also reflects the culture of its times. Private law of 19th century was no exception. This study shows that political partitions of Poland has divided also polish perception of family and fatherhood. This work examines the problem of parallel visions of polish fatherhood through the lens of the early civil law codifications. New private laws were starting point for a change in paternal power. These modernization has had their own speed and energy separate in each partition area. Focusing on paternity as a category of family history, this article shows the changing borders of paternal power and responsibility which brings new approach to understanding of how private acts were governed by laws of the state.
Different ranges of paternal power according to binding regulations existing in Polish territories in the first half of the 19th century
Keywords: fatherhood; codification; family; private law; 19th century